19. Evaluation of subchronic toxicity of diabetna capsules in experimental animals - Oanh, Le Hong; Chau, Hoang Minh; Manh, Khuat Van; Thuong, Phuong Thien; Duong, Dau Thuy; Trang, Tran Quynh; Anh, Pham Thi Van; Hang, Dinh Thi Thu; Thuy, Nguyen Thi (Tạp chí Nghiên cứu Y học, 2024)
This research aimed to evaluate the subchronic toxicity of Diabetna capsules through oral administration in experimental animals. The subchronic toxicity was studied in Wistar rats with oral doses of 0.72 g/kg/day (equal to recommended human dose) and 2.16 g/kg/day (3 times as high as recommended human dose) in consecutive 12 weeks, following guidance from the World Health Organization and Organisation for Economic Co-operation and Development. Our result showed that Diabetna capsules had no deleterious effect on hematological parameters, hepato-renal functions, macroscopic and microscopic images of the livers and kidneys of Wistar rats. In conclusion, Diabetna capsules did not produce subchronic toxicity in experimental animals.